SEAFLOOR ENVIRONMENTAL CHANGES RESULTING FROM NINETEENTH CENTURY RECLAMATION IN MISHOU BAY, BUNGO CHANNEL, SOUTHWEST JAPAN - Amano A.; Iwamoto N.; Inoue T.; Inouchi Y. (My University, 2006)
This study reconstructed environmental changes to the seafloor associated with reclamation in Mishou Bay, Bungo Channel, Japan, based on measurements of sediment grain size, organic matter and sulfur contents of surface sediments and data from sediment cores. Grain size within sediment cores from the middle of Mishou Bay decreased from the beginning of the 1800s to the 1900s. In contrast, a grain size profile from the river mouth shows a gradual increase in grain size up through the sediment core. These changes in grain size indicate a decrease in tidal current velocity within the middle of the bay and that the delta system is gradually prograding from the river mouth. Records of organic matter composition and sulfur contents indicate that the effect of the river on seafloor sedimentation became stronger during the nineteenth century. These changes are related to reclamation during the late 1700s and 1800s. The decrease in sea area resulting from reclamation probably led to a decrease in tidal prism and current velocity. It is likely that the increasing effect of river water on sedimentation is associated with reclamation-related progradation of the river delta system. © Springer-Verlag 2006.
Keywords: GRAIN SIZE; RECLAMATION; SEDIMENTARY ENVIRONMENT; TOTAL ORGANIC CARBON; TOTAL SULFUR